Magnetoreception and Magnetosomes in Bacteria - Schüler, Dirk.; Schüler, Dirk. (Microbiology Monographs,, 2007)
Magnetoreception or magnetotaxis in bacteria was discovered only some 30 years ago. All magnetotactic bacteria, which occur in many environments and display a remarkable diversity, synthesize magnetosomes, complex intracellular organelles that contain magnetic iron crystals. Recent developments in the research on magnetotactic bacteria are presented in this volume. Included are reviews on the formation and organization of magnetosomes, the genes controlling magnetosome biomineralization, and new cryogenic techniques to visualize novel cytoskeleton structures. Described here are potential nanobiotechnological applications of the magnetosome crystals, which have magnetic and crystalline characteristics unmatched by their inorganic counterparts. Related topics such as the impact of biogenic magnetic crystals in geobiology and paleomagnetism also are discussed. The aim of the book is to provide a broad survey of this multidisciplinary field and to inspire future research on these fascinating organisms.